2012
DOI: 10.3988/jcn.2012.8.2.139
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison between Clinical Disabilities and Electrophysiological Values in Charcot-Marie-Tooth 1A Patients with PMP22 Duplication

Abstract: Background and PurposeCharcot-Marie-Tooth disease (CMT) type 1A (CMT1A) is the demyelinating form of CMT that is significantly associated with PMP22 duplication. Some studies have found that the disease-related disabilities of these patients are correlated with their compound muscle action potentials (CMAPs), while others have suggested that they are related to the nerve conduction velocities. In the present study, we investigated the correlations between the disease-related disabilities and the electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
(39 reference statements)
3
16
0
Order By: Relevance
“…We found that changes on NCS are not related either to QoL or symptoms in our group of patients. This has been shown previously in other neuropathies such as Charcot‐Marie‐Tooth disease (Kim et al ., ) .…”
Section: Discussionmentioning
confidence: 97%
“…We found that changes on NCS are not related either to QoL or symptoms in our group of patients. This has been shown previously in other neuropathies such as Charcot‐Marie‐Tooth disease (Kim et al ., ) .…”
Section: Discussionmentioning
confidence: 97%
“…Clinical deficits correlate more with decrease in compound motor action potential (CMAP) and sensory nerve action potential (SNAP) amplitudes as a consequence of axonal loss, than motor or sensory NCVs which reflects the degree of demyelination [5,36,40,81]. Verhamme et al [78] observed that CMAP amplitude reduced over time with disease progression, while NCV remained fairly constant in adults with CMT1A.…”
Section: Electrophysiologymentioning
confidence: 97%
“…10,11 Here, we identified a CMT1A family with wide phenotypic difference. Subsequent genetic study identified that a patient with severe clinical symptoms had unusual PMP22 triplication.…”
Section: Introductionmentioning
confidence: 94%